Mixed initiative control of autonomous vehicles - Kumar, Vijay R.; Loizou, Savvas (My University, 2007)
While there is extensive work on motion planning and control for navigation tasks with guarantees, there is no systematic way for human operators to modify the resulting plans without losing the guarantees. In this paper we propose a systematic way of composing behaviors resulting from human inputs with behaviors derived from navigation functions. The proposed controller is based on a new class of navigation function based controllers that posses weak Input-to-State stability properties. The resulting system has analytically guaranteed safety and convergence properties. The feasibility of the proposed methodology is demonstrated through simulation examples and hardware experiments.
Keywords: Computer simulation; Navigation; Vehicles